Tìm tập xác định
y = 1 - 2cosx / sin3x - sinx
y= 2 / cosx - cos3x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1: ĐKXĐ: 3-cosx>0
=>cosx<3(luôn đúng)
2: ĐKXĐ: 1-sin 3x>=0
=>sin 3x<=1(luôn đúng)
3: ĐKXĐ: sin x<>0 và 2x<>pi/2+kpi
=>x<>kpi và x<>pi/4+kpi/2
4: ĐKXĐ: 2x-1>=0
=>x>=1/2
b: \(\Leftrightarrow2\cdot\cos2x\cdot\cos x+2\cdot\sin x\cdot\cos2x=\sqrt{2}\cdot\cos2x\)
\(\Leftrightarrow2\cdot\cos2x\left(\sin x+\cos x\right)=\sqrt{2}\cdot\cos2x\)
\(\Leftrightarrow\sqrt{2}\cdot\cos2x\cdot\left[\sqrt{2}\cdot\sqrt{2}\cdot\sin\left(x+\dfrac{\Pi}{4}\right)-1\right]=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\cos2x=0\\\sin\left(x+\dfrac{\Pi}{4}\right)=\dfrac{1}{2}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=\dfrac{\Pi}{2}+k\Pi\\x+\dfrac{\Pi}{4}=\dfrac{\Pi}{6}+k2\Pi\\x+\dfrac{\Pi}{4}=\dfrac{5}{6}\Pi+k2\Pi\end{matrix}\right.\)
\(\Leftrightarrow x\in\left\{\dfrac{\Pi}{4}+\dfrac{k\Pi}{2};\dfrac{-1}{12}\Pi+k2\Pi;\dfrac{7}{12}\Pi+k2\Pi\right\}\)
c: \(\Leftrightarrow2\cdot\sin2x\cdot\cos x+\sin2x=2\cdot\cos2x\cdot\cos x+\cos2x\)
\(\Leftrightarrow\sin2x\left(2\cos x+1\right)=\cos2x\left(2\cos x+1\right)\)
\(\Leftrightarrow\left[{}\begin{matrix}\sin2x=\cos2x=\sin\left(\dfrac{\Pi}{2}-2x\right)\\\cos x=-\dfrac{1}{2}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{\Pi}{8}+\dfrac{k\Pi}{4}\\\\x=-\dfrac{2}{3}\Pi+k2\Pi\\x=\dfrac{2}{3}\Pi+k2\Pi\end{matrix}\right.\)
1. \(sin\left(\dfrac{\pi}{3}-x\right)\ne0\Leftrightarrow\dfrac{\pi}{3}-x\ne k\pi\Leftrightarrow x\ne\dfrac{\pi}{3}-k\pi\)
2. \(cos2x\ne0\Leftrightarrow2x\ne\dfrac{\pi}{2}+k\pi\Leftrightarrow x\ne\dfrac{\pi}{4}+\dfrac{k\pi}{2}\)
3. \(\sqrt{1+sinx}-\sqrt{2}\ge0\Leftrightarrow1+sinx\ge2\Leftrightarrow sinx\ge1\Leftrightarrow sinx=1\Leftrightarrow x=\dfrac{\pi}{2}+k2\pi\)
4. \(\sqrt{2-2cosx}-2\ne0\Leftrightarrow2-2cosx\ne4\Leftrightarrow cosx\ne-1\Leftrightarrow x\ne\pi+k2\pi\)
5. \(1-\sqrt{1+sin3x}\ne0\Leftrightarrow sin3x\ne0\Leftrightarrow3x\ne k\pi\Leftrightarrow x\ne\dfrac{k\pi}{3}\)
ĐKXĐ: ...
\(sin3x-cos3x+sinx+cosx=\dfrac{sin3x-cos3x+sinx+cosx}{\left(sin3x+cosx\right)\left(cos3x-sinx\right)}\)
\(\Rightarrow\left[{}\begin{matrix}sin3x-cos3x+sinx+cosx=0\left(1\right)\\\left(sin3x+cosx\right)\left(cos3x-sinx\right)=1\left(2\right)\end{matrix}\right.\)
(1) \(\Leftrightarrow3sinx-4sin^3x-4cos^3x+3cosx+sinx+cosx=0\)
\(\Leftrightarrow sinx+cosx+sin^3x+cos^3x=0\)
\(\Leftrightarrow sinx+cosx+\left(sinx+cosx\right)\left(1-sinx.cosx\right)=0\)
\(\Leftrightarrow\left(sinx+cosx\right)\left(2-sinx.cosx\right)=0\)
\(\Leftrightarrow sinx+cosx=0\) (loại)
(2) \(\Leftrightarrow sin3x.cos3x-sinx.cosx-sin3x.sinx+cos3x.cosx=1\)
\(\Leftrightarrow\dfrac{1}{2}sin6x-\dfrac{1}{2}sin2x+cos4x=1\)
\(\Leftrightarrow\dfrac{1}{2}\left(3sin2x-4sin^32x\right)-\dfrac{1}{2}sin2x+1-2sin^22x=1\)
\(\Leftrightarrow sin2x-2sin^32x-2sin^22x=0\)
\(\Leftrightarrow-sin2x\left(2sin^22x+2sin2x-1\right)=0\)
\(\Leftrightarrow...\)
\(\frac{\left(sin3x+cosx\right)sin3x+\left(cos3x+sinx\right)cos3x}{cos4x}\)
\(=\frac{sin^23x+sin3x.cosx+cos^23x+cos3x.sinx}{cos4x}=\frac{1+sin3x.cosx+cos3x.sinx}{cos4x}\)
\(=\frac{1+sin4x}{cos4x}=\frac{sin^22x+cos^22x+2sin2x.cos2x}{cos^22x-sin^22x}=\frac{\left(cos2x+sin2x\right)^2}{\left(cos2x-sin2x\right)\left(cos2x+sin2x\right)}\)
\(=\frac{cos2x+sin2x}{cos2x-sin2x}=\frac{1+\frac{sin2x}{cos2x}}{1-\frac{sin2x}{cos2x}}=\frac{1+tan2x}{1-tan2x}\)
ĐKXĐ:
a.
\(sin3x-sinx\ne0\)
\(\Leftrightarrow sin3x\ne sinx\Leftrightarrow\left\{{}\begin{matrix}3x\ne x+k2\pi\\3x\ne\pi-x+k2\pi\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x\ne k\pi\\x\ne\frac{\pi}{4}+\frac{k\pi}{2}\end{matrix}\right.\)
b.
\(cos3x-cosx\ne0\Leftrightarrow cos3x\ne cosx\)
\(\Leftrightarrow\left[{}\begin{matrix}3x\ne x+k2\pi\\3x\ne-x+k2\pi\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x\ne k\pi\\x\ne\frac{k\pi}{2}\end{matrix}\right.\) \(\Leftrightarrow x\ne\frac{k\pi}{2}\)